Postoperative pain assessment, and opioid utilisation after hospital discharge following colectomy - Baamer, Reham (2024)
Background and aims Opioids have an established role in the management of postoperative pain; however, inappropriate opioid utilisation is evident, influenced by several factors including the overreliance on unidimensional pain assessment tools to guide opioid dosing. This thesis aims to advance the understanding of the management of postoperative pain, including pain assessment, opioid utilisation trends and persistent postoperative opioid use (PPOU) following colectomy.